The clinical profle, hematological parameters and liver transaminases of dengue NS1 Ag positive patients admitted to Jafna Teaching Hospital, Sri Lanka - Jayadas, T.T.P.; Kumanan, T.; Arasaratnam, V.; Gajapathy, K.; Surendran, S.N. (BMC Research notes, 2019)
Objective: Objective of the study is to evaluate the on-admission day symptoms and signs, clinical, hematological parameters and liver transaminases of the dengue NS1 positive patients who got admitted on diferent clinical phases [Febrile phase (day 1–3) and Critical phase(day 4–5)] of dengue at medical wards of Jafna Teaching Hospital. Results: Blood samples were collected from 150 suspected dengue patients from day 1 to 5 of the illness. Seventy eight patients were positive for dengue NS1, according to the WHO proposed dengue clinical phase framework 37 patients were from febrile phase and 41 patients from critical phase. Patients who admitted on critical phase frame work sufered from leukopenia and thrombocytopenia. Nine patients had the evidence of leakage with fever and the leakers had signifcant rise in hemoglobin, hematocrit and liver transaminase levels which are considered as severe form of the disease
Keywords: Clinical profle; Dengue; Hematological parameters; Liver transaminases; NS1 antigen; Sri Lanka